Cathelicidin as a link between sarcoidosis and tuberculosis - Korucu, Ercan; Pur Ozyigit, Leyla; Ortakoylu, Mediha Gonenc; Bahadir, Ayse; Akalin, Esma Seda; Kara, Asuman; Uzun, Hafize; Onal, Burak; Caglar, Emel (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2015)
ABSTRACT Setting: Sarcoidosis and tuberculosis share notable clinical, radiological, histological, and immunological similarities. The importance of vitamin D has long been investigated in these two granulomatous lung diseases. Cathelicidin is an antimicrobial peptide of the innate immune system, directly induced by vitD3. Objective: To evaluate the role of cathelicidin in sarcoidosis and tuberculosis development. Design: The study included 30 consecutive patients with active lung tuberculosis, 30 patients with sarcoidosis, and 20 healthy controls. 25-hydroxyvitamin D [25(OH)D] and cathelicidin levels were measured in blood samples. Results: Vitamin D levels were significantly higher (p<0.001) in tuberculosis patients (22.5±9.96 ng/ml) than in sarcoidosis patients (11.75±8.92 ng/ml). Severe vitamin D deficiency was as frequent as 47% in sarcoidosis patients compared to only 3% in tuberculosis patients. Cathelicidin levels were significantly higher in the control group (120.37±41.03 pg/ml) than in sarcoidosis (67.68±38.03 pg/ml) and tuberculosis (68.74 ±39.44 pg/ml) patients (p<0.001). However, no significant difference in cathelicidin levels was observed between tuberculosis and sarcoidosis patients (p=0.966). The optimum cathelicidin cut-off value to distinguish sarcoidosis patients from healthy controls was 107.14 pg/ml (sensitivity 81.5%, specificity 71.2%). Conclusion: Cathelicidin appears to play different roles in the development of granulomatous lung disease.